Electrochemical electron transfer and its relation to charge transport in single molecule junctions - Hromadová, Magdaléna; Vavrek, František (Current opinion in electrochemistry, 2020)
Ability to control charge transport at nanometer scale lies in the heart of design of fast reliable electronic devices. Molecular electronics thrive to use functional molecules for such transport. If the molecule contains redox center(s), a diode-like or transistor-like behavior can be easily explored by controlling not only the voltage difference between two metallic contacts of the molecular junction but also the potential of one of the contacting electrodes with respect to some reference. Thus, one needs to understand the relationship between electrochemical electron transfer and charge transport in metal–molecule–metal junctions. This review presents latest theoretical approaches toward understanding of such relationship and discusses pivotal experimental works to validate them. Tunneling and hopping pathways may operate in parallel (two-channel model), but experimental conditions dictate the channel preference.